Processo de entrada de instituições de ensino superior para o Brasil: o caso da Laureate International Universities - Bulgarão, Renato Márcio (2015)
The aim of this study is to show the cultural influences in the process of internationalization of the international Laureate network for Brazil. The approach of the internationalization process of higher education, was the method of qualitative research case study type, focusing on the Laureate International universities. The technique used was content analysis and it was verified and interpreted the content that then provided clarification on the proposed objectives Bardin (2011). The QSR NVivo 10 software for Windows helped analyze grouping converging ideas in dendagramas (words of trees), which were assessed 17 key terms to elucidate this research. The survey showed that in case of Laureate International Universities, cultural, administrative, geographic and economic factors, influenced partially in the input process of higher education institutions in Brazil. Some factors appeared highlighted as cultural change with strategic deployments in the internationalization process: need for improvements in the management, increment of skills to commercial rivalry by region, and advance of economic performance in different infrastructure.